Is There a Place for Surgical Revascularization in Acute Myocardial Infarction? - Olena K. Gogayeva; Mykola L. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2025)
Rapid restoration of coronary blood flow is extremely important in patients with acute myocardial infarction (AMI). Timely reperfusion, performed within the first hours from the onset of angina pectoris, not only improves outcomes but also prevents life-threatening complications. In AMI, preference is given to percutaneous coronary interventions and thrombolytic therapy, while emergency surgical myocardial revascularization is performed for 1.2–5 % of patients.Aim- to determine the role of surgical myocardial revascularization in AMI according to modern literature.Materials and methods. Analysis of recent clinical guidelines and literature on surgical treatment of AMI.Conclusions. In patients with acute MI, emergency surgical myocardial revascularization is possible. The treatment strategy for patients with AMI is selected individually by the Heart Team, based on assessment of pain duration, hemodynamic status, complexity of coronary artery disease, and the presence of mechanical and thrombotic complications. The priority of emergency cardiac surgery increases when stenting of the infarct-related artery is impossible, in cases of multivessel coronary artery disease, large volume of ischemic myocardial damage, or mechanical complications. Further clinical studies are necessary to determine the optimal timing for cardiac surgery in the context of AMI with and without ST-segment elevation.